Hypoxia and platelet lysate sustain differentiation of primary horse articular chondrocytes in xeno-free supplementation culture. (20th December 2022) - Ravanetti, Francesca; Saleri, Roberta; Martelli, Paolo; Andrani, Melania; Ferrari, Luca; Cavalli, Valeria; Conti, Virna; Rossetti, Alessio Pio; De Angelis, Elena; Borghetti, Paolo
Abstract: Currently, the main limitation for the use of adult differentiated chondrocytes in cell-based therapy and tissue engineering for the repair of articular cartilage is the difficulty of maintaining their state of differentiation during cell expansion. The adult articular cartilage has no direct blood supply, and local oxygen concentrations range from 5%–10% at the surface near the synovial fluid to less than 1% in the deep layer. Low oxygen tension is currently considered an important environmental condition for chondrocytes, and hypoxia has been explored as a signal potentially promoting differentiation and matrix deposition. In the present study, hypoxia and PL supplementation were studied to maintain differentiation in adult articular chondrocytes. Freshly isolated equine articular chondrocytes were grown in monolayer culture at a low seeding density (condition favoring proliferation and dedifferentiation) and in alginate beads (3D culture condition maintaining chondrocyte differentiation) both in normoxic and hypoxic conditions and in various conditions of supplementation or deprivation (fetal bovine serum [FBS]- and PL-free; 10% FBS; 5% PL; 10% PL). Results demonstrated that hypoxia is a micro-environmental condition that reduces chondrocyte dedifferentiation or maintains differentiation during in vitro expansion, as shown by the sustained expression of differentiation markers ( COL2, ACAN, SOX9, HIF1a ) and the reduction of dedifferentiation marker expression ( COL1, RUNX2 ). In association with hypoxia, PL supplementation demonstrated a positive effect on chondrocyte differentiation in association with hypoxia. This promising result should be confirmed in other conditions of chondrocyte differentiation before proposing PL as a complete alternative to xenogenic serum for the expansion of articular chondrocytes. Highlights: The micro-environmental factors are crucial to limit the loss of differentiation of chondrocytes for tissue engineering. Hypoxia is an alternative method to reduce chondrocyte dedifferentiation during in vitro expansion in 2D and 3D cultures. Hypoxia combined with 5% PL supplementation could be a promising to maintain the chondrocyte phenotype in culture. PL and hypoxia can represent an alternative to FBS to sustain chondrocyte proliferation and modulate their differentiation.